An Unrealistic ‘Mission Impossible’? Surveying Principals’ Interpretations and Local Solutions for L2-mediated EFL in Finnish Adult Basic Education - Suomela, Antti (Umeå University/Nordic Association of English Studies, 2025)
Finnish Adult Basic Education (ABE) comprises primary and lower secondary education designed to improve adult immigrants’ participation. Completing the entire syllabus and graduating with a Finnish basic education certificate is helpful for many adult immigrants without prior basic education in finding work, continuing studies at the upper secondary level, and applying for Finnish citizenship. English has potential utility for integration in the Nordic countries, yet adult immigrants’ foreign language studies, and Finnish ABE, have been little studied. Recent government reports have indicated that ABE students seem to face exceptional challenges in their language studies, particularly their compulsory advanced syllabus English studies. The present survey study (n=35) targeting principals of ABE institutions examines institution-level foreign language education practices and principals’ views on language education. The findings indicate that ABE English education is rapid-paced, relies on a local teaching language that students have only learned for a few years, and may lack suitable instructional materials and tests. Most principals are not convinced that their students graduate with English skills sufficient for language needs in working life or upper secondary education. Varied local interpretations of national guidelines lead to inequity in language learning opportunities. The findings highlight the significance of aligning materials and local and national policies with student diversity and the evolving role of English in the Nordics.